Seed size selection from M3 mutant soybean offspring of Kipas Merah Bireun variety in Aceh province - ZUYASNA ZUYASNA; M. ADIE MUCHLISH; EFENDI EFENDI; ZURAIDA ZURAIDA (Jurnal Natural, 2022)
Kipas Merah Bireun is one of the superior soybeans which was once widely cultivated in Bireun Regency, Aceh Province, used to be as a centre of origin of Kipas Merah Bireun variety. The weaknesses of the Kipas Merah Bireun variety are relatively small seed size (dry weight 12 g/100 seeds), long harvest period and less resistance to drought stress. Therefore it is necessary to improve the quality of Kipas Merah Bireun variety soybeans in order to get soybeans with better properties, one way is to use mutation techniques. The objectives of the study reported here were to evaluate the genetic variability for seed size of single plant selection for large seed in the mutants of gamma irradiated population. The research successfully selected 41 lines soybean mutant with both of high weight seed per plant and large seed size. Several mutant lines of Kipas Merah Bireun were promising to be investigated and developed further in accordance with attempts to increase productivity in Aceh province. Therefore, further research is needed to see how the growth and production of selected mutant soybeans with large seeds in this study in various locations and planting seasons.